UN peacekeeping in Lebanon and Somalia: international and national legal perspectives - Murphy, Ray (2001)
The initial focus of the thesis is on Ireland, a small militarily neutral state, but one with a long tradition of contributing to peacekeeping operations. Despite its significant contribution to peace support operations to date, there is little research on the past and future implications of this for Ireland. This thesis seeks to address some of the key legal and political issues confronting Ireland, and to provide a unique perspective on the dilemmas and problems confronting many small states of the UN in the post cold war era. The thesis uses two case studies, Somalia and Lebanon, to conduct a comparative analysis of traditional peacekeeping and that of peace enforcement The conduct of UN forces in Somalia, and the outcome of the UN mandated operations there, had a profound effect on the willingness of states to support UN peace support operations in the post cold war period. UNOSOM II was one of the most ambitious and controversial multidimensional operations ever mounted by the UN. It reflected the optimism associated with the dawn of a 'new world order' and an effective Security Council. The UN operation in Lebanon (UNIFIL), in contrast, was a less ambitious traditional peacekeeping mission, but it too was controversial and the Force encountered serious difficulties implementing the apparently more straightforward mandate. Both operations show that whatever the nature of a peace support operation, its role and effectiveness is dependent upon support from the Security Council. Without political support and adequate resources, especially at the time of its establishment, a UN force remains at the mercy of the parties to the conflict. Both operations also highlighted serious difficulties that arise in the command and control of UN peace support operations, although the larger more complex UNOSOM II mission presented significantly more serious dilemmas in this regard. These problems are often exacerbated by deficiencies in the municipal laws and domestic political concerns of contributing states. An important distinguishing feature between traditional peacekeeping operations and that of more robust peace enforcement operations is the policy regarding the use of force. Nevertheless, both Lebanon and Somalia presented remarkably similar difficulties regarding devising and adopting appropriate rules of engagement, and the differing interpretations of what action justified the resort to, and the degree of force deemed appropriate in a UN multi-national operation. The thesis seeks to draw lessons from the experiences of UNIFIL and UNOSOM in regard to these and related issues. The matter of the applicability of international humanitarian law to UN forces was also relevant to both sets of operations. Despite the recent adoption of the Convention on the Protection of UN Personnel, and a Secretary-General's bulletin on the applicability of humanitarian law to UN forces, the situation remains unsatisfactory.